ANALISIS OPTIMALISASI PENJUALAN MENGGUNAKAN METODE SIMPLEKS PADA USAHA KECIL MENENGAH - Matheus Supriyanto Rumetna; Tirsa Nina Lina; Jalminj Tindage (LPPM Universitas Widya Dharma, 2022)
Competition in the business world is now getting faster, coupled with the Covid-19 pandemic, making many small-scale businesses suffer losses and close their businesses. One of them is the business owned by Mr. Wartono which also experienced the same thing plus the problem related to determining the optimum sales production amount, so as to generate maximum sales profit. This problem can be solved using the simplex method which is one part of the Linear Program and utilizes information technology, namely POM-QM software for Windows V5. The purpose of using OT, especially the simplex method, is to assist in decision making. The results of this study provide optimal profits from the amount of sales production.